Consular Diptychs and Buddhist Diptychs: Another Way of Exploring Western Elements in Gandhara Art - Hameed, Muhammad (Ancient Pakistan, 2017)
The work in hand discusses the usage of diptych type objects in Western world and in Gandhara. The basic purpose of the research is to determine the origin of diptychs in this part of the world that when and why such objects were manufactured in Gandhara? To answer these questions diptychs in the Western World, referred to as the ‘Consular Diptychs’, are examined. The study throws light on their origin, function, shape, technique, material, iconography and significance. Comparative study of similarities and dissimilarities between the Western diptychs and the Gandharan diptychs is also a part of the investigation through which an attempt has also been made to establish a link between these two traditions. Moreover, final statement is formulated regarding origin of diptych type objects in Gandhāra. At the end, the Basket Man Type Buddhist Diptychs are discussed. This section primarily introduces these diptychs along with description of their iconographic details. Examples from Gandhāran reliefs are also included to analyze pictorial representation.